On the law relating to the realization of judgments and decrees, with special reference to judgments and decrees against tenant-farmers - Dodd, William H. (Statistical and Social Inquiry Society of Ireland, 1879)
When an advocate has carried a case to a successful termination in court, and the judgment or decree has been obtained, the anxious client often asks: ?How am I to get it realized?? He is put off jokingly with the answer??That is entirely for yourself. All we can get for you is the verdict?. There is an amount of grim truth, however, in the answer, which rather spoils the jest. And it would seem as if our legal reformers had adopted the answer as one eminently just and right. For of late years many efforts at legislation have been made, and various Acts have been passed, with a view to facilitating the trial of actions. But comparatively little attention has been bestowed on what takes place after verdict had and judgment given. And yet this portion of our legal machinery needs adjustment and reform more than any other. 'Die difficulties in the way of enforcing a judgment against a tenant, so as to realize the amount out of his interest in his farm, are very numerous.
Read before the Society, 10 December 1878
Keywords: Judgments; Decrees; Irish tenant-farmers; Litigation process; 314.15